(55-y)y=684

Simple and best practice solution for (55-y)y=684 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (55-y)y=684 equation:


Simplifying
(55 + -1y) * y = 684

Reorder the terms for easier multiplication:
y(55 + -1y) = 684
(55 * y + -1y * y) = 684
(55y + -1y2) = 684

Solving
55y + -1y2 = 684

Solving for variable 'y'.

Reorder the terms:
-684 + 55y + -1y2 = 684 + -684

Combine like terms: 684 + -684 = 0
-684 + 55y + -1y2 = 0

Factor a trinomial.
(-36 + y)(19 + -1y) = 0

Subproblem 1

Set the factor '(-36 + y)' equal to zero and attempt to solve: Simplifying -36 + y = 0 Solving -36 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + y = 0 + 36 Combine like terms: -36 + 36 = 0 0 + y = 0 + 36 y = 0 + 36 Combine like terms: 0 + 36 = 36 y = 36 Simplifying y = 36

Subproblem 2

Set the factor '(19 + -1y)' equal to zero and attempt to solve: Simplifying 19 + -1y = 0 Solving 19 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -1y = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -1y = 0 + -19 -1y = 0 + -19 Combine like terms: 0 + -19 = -19 -1y = -19 Divide each side by '-1'. y = 19 Simplifying y = 19

Solution

y = {36, 19}

See similar equations:

| 6g+3g-10+3=47 | | -6x+5(-x+8)=139 | | 15(16)-14=c | | h+13.5=-13.5 | | 15(10)-14=c | | 15(2)-14=c | | 4x-9=4x+12 | | -8=3u-5 | | 10y-3y=7 | | (X+2)(x+10)=20 | | -2+9=1x+42 | | 7t+1+5t+8=162 | | -8v+3(v+8)=29 | | -45+15(x)=0 | | -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x | | -2v-6v=-16 | | 0=4e+4 | | 36-3x=312-x | | 7t+1=162 | | 2x-3+21=-3 | | -45+15(15)=x | | y=2000+2500x-25000+2000x | | 2-(x-3)+6=8 | | 5n+9=54 | | -45+15(1)=x | | a-7a+3=6a+3 | | 1+3n+6=-5 | | (3+3i)+(2+4i)= |

Equations solver categories